Peran Hukum Perkawinan Dalam Optimalisasi Perlindungan Hak Anak - Syarifuddin Lubisa; Putra halomoan Hasibuan (CV. ITTC INDONESIA, 2026)
Marriage, as a social and legal institution, plays a crucial role in shaping the family environment, which serves as the primary setting for a child's growth and development. Marriage law in Indonesia not only governs the relationship between husband and wife but also serves to protect the rights of children born from such marriages. This research aims to examine the role of marriage law in optimizing the protection of children's rights in Indonesia by analyzing the prevailing legal provisions and the challenges in their implementation. The research method used is normative-empirical through literature studies and field observations. The findings show that although legal foundations such as Law No. 1 of 1974 and Law No. 35 of 2014 are in place, there are still obstacles to child protection due to early marriage and children born out of wedlock. Optimizing the protection of children's rights requires synergy among the government, families, communities, and legal institutions in law enforcement and public awareness efforts to ensure sustainable child protection.